Comparative genomics of the streptococcal mobilome reveals class-specific integration, mobility and antimicrobial resistance cargo - Kaiwei Nie; Xingyang Dai; Jiaqi Zhao; Mengjie Qi; Cai Yin; Xiaoming Wang; Liping Wang; Jinhu Huang (One Health Advances, 2026)
Abstract Mobile genetic elements (MGEs) drive genome plasticity, horizontal gene transfer, and antimicrobial resistance (AMR) dissemination in Streptococcus , yet genus-wide comparisons across major MGE classes remain limited. Here, we analyzed 1961 complete chromosomes from 60 Streptococcus species together with 225 plasmids, and compared integrative and conjugative elements (ICEs), integrative and mobilizable elements (IMEs), prophages, and plasmids with respect to host distribution, boundary-supported integration-site preference, mobility-associated modules, representative backbones, and AMR cargo. We identified 1172 ICEs, 2362 IMEs, 3397 prophages, and 225 plasmids, and found that the streptococcal mobilome was strongly partitioned by host lineage, with ICEs and IMEs enriched in Streptococcus dysgalactiae , prophages in Streptococcus pyogenes , and plasmids in Streptococcus suis . Integrated MGEs also displayed class-specific hotspot hierarchies after boundary inspection: ICEs were highly concentrated at rplL , with secondary hotspots at rlmD and rpmH ; IMEs were dominated by tRNA-associated sites together with rpsI and rpmG , whereas prophages occupied a broader hotspot spectrum centered on tRNA, rpmE , rpsD , hlpA , and mutL . Mobility analyses further distinguished the classes, showing that ICEs retained a narrow repertoire of conjugative backbones dominated by typeFATA, IMEs displayed the broadest relaxase diversity, and plasmids were mainly non-mobile or mobilizable. Representative family analyses resolved recurrent backbone types within each class, whereas AMR cargo was concentrated in ICEs and plasmids and was further stratified by host species. Together, these findings reveal a previously underappreciated class- and host-dependent organization of the streptococcal mobilome and its AMR cargo.